Dora's big dig - Inches, Alison; Roper, Robert (London : Simon and Schuster/Nickelodeon, 2007)
Dora and Boots uncover an ancient treasure and wants to take it to her mom who is an archaeologist.
"Based on the TV series Dora the Explorer"--T.p. verso.
1.8
K-3
Keywords: Antiquities -- Juvenile fiction; Dora the Explorer (Fictitious character) -- Juvenile fiction; Explorers -- Juvenile fiction; Antiquities. -- Fiction; Dora the Explorer (Fictitious character) -- Fiction; Explorers -- Fiction; Antiquities. -- Fiction; Dora the Explorer (Fictional character) -- Fiction; Explorers -- Fiction; Radio and television novels